Sport online - Intille, S.
The future of sport on the Internet is promising. This paper takes a look at present day Internet technologies and services, evaluating them based on how well they capture the most appealing characteristics of sport entertainment. It then outlines the computer and communication technologies that designers will use to overcome some limitations of the current systems. Finally, it discusses some future applications that have the potential to change the nature of sport as we know it.